A Few Reports Related Settlement Activities After Greek-Turkısh Population Exchange : The Case Of Antalya - Arslan, Aslı (Osman Kose, 2022)
According to the Agreement on the Exchange of Turkish-Greek People, which was adopted after the Lausanne Peace Treaty, the decision on the mandatory exchange of Greek Orthodox people in Anatolia and Muslim people in Greece caused a large migration of the Muslim-Turkish community. These major migration and migrant issues, which are a matter for the state in their own right, have tried to be resolved in a short time by establishing a relevant ministry, publishing regulations, and instructions while using certain criteria. Those who arrived earlier than the exchange, who needed help within the borders of Anatolia, whose homes were burned down during the war, and refugees from different places were caught this wave of migration. As a result of the fact that the country has not yet reached prosperity due to the fact that it has just come out of the war, internal displacement, issues related to houses and lands vacated from the Greeks, economic, administrative, legal, and many other issues are considered to cause problems in the resettlement of migrants and prolong their resettlement. After the exchange, residential areas were determined according to the work done by the exchanged immigrants, and housing activities began to be carried out by the housing directorates in these regions. Antalya province has been one of these regions. İmmigrants who are forced to reside in Antalya has experienced problems due to some practices. In this study, in the province of Antalya, experiences of the immigrants, during the settlement process such as; the scarcity of abandoned goods, inability to find space for housing, if there are failures of the settlement managers, officers during the settlement process, whether not keeping the housing books incomplete or not sending the records to the population directorates were evaluated with the parts reflected in the Governor’s and Inspector General’s reports. © 2022, Osman Kose. All rights reserved.
MÜBADELE SONRASI İSKÂN FAALİYETLERİNE İLİŞKİN BİRKAÇ RAPOR: ANTALYA ÖRNEĞİ
Keywords: Antalya; Exchange; Report; Settlement